2020
DOI: 10.3389/fpls.2020.01219
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Deficiency Significantly Affected Plant Growth and Development as Well as microRNA-Mediated Mechanism in Wheat (Triticum aestivum L.)

Abstract: It is well studied that potassium (K +) deficiency induced aberrant growth and development of plant and altered the expression of protein-coding genes. However, there are not too many systematic investigations on root development affected by K + deficiency, and there is no report on miRNA expression during K + deficiency in wheat. In this study, we found that K + deficiency significantly affected wheat seedling growth and development, evidenced by reduced plant biomass and small plant size. In wheat cultivar A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…In this study, low K promotes both lateral and primary root growth while reduced the total root length. Similar results were also observed in wheat (Thornburg et al, 2020), and almost the opposite result was observed in cotton (Fontana et al, 2020). Although the number of lateral roots and the primary root length increased, the root system was inhibited under K deficiency treatment.…”
Section: The Peanut Root System Has a Specific Response To N Deficiency And K Deficiency Stressessupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, low K promotes both lateral and primary root growth while reduced the total root length. Similar results were also observed in wheat (Thornburg et al, 2020), and almost the opposite result was observed in cotton (Fontana et al, 2020). Although the number of lateral roots and the primary root length increased, the root system was inhibited under K deficiency treatment.…”
Section: The Peanut Root System Has a Specific Response To N Deficiency And K Deficiency Stressessupporting
confidence: 82%
“…These N deficiency-induced growth inhibition phenomena were also observed in other plant species, including potatoes (Xie et al, 2018). Studies have also shown that 0.02 mM K + can induce aberrant growth and development in cotton (Fontana et al, 2020) and wheat (Thornburg et al, 2020), which probably due to the reduction of chlorophyll content and photosynthetic capacity.…”
Section: Discussion N and K Deficiency Significantly Inhibited The Growth And Development Of Peanut Seedlingsmentioning
confidence: 63%
See 1 more Smart Citation
“…The major goal of this study was to investigate the effects of difenoconazole, uptaken by wheat roots, on the growth of whole seedling plants. However, since the growth of the roots is difficult to directly observe with soil culture, this study was conducted by hydroponics according to previously described methods [16,17].…”
Section: Plant Materials and Culture Conditionsmentioning
confidence: 99%
“…Seeds of the wheat cultivar Bainong 207 (bred by the Wheat Genetic Improvement Research Center of Henan Institute of Science and Technology) were selected in this study. The seed treatment and planting procedures followed our previous reports [16,17]. Briefly, the wheat seeds were sterilized in 10% hydrogen peroxide (H 2 O 2 ) for 10 min and then rinsed with distilled water 3-5 times to eliminate the H 2 O 2 residues.…”
Section: Plant Materials and Culture Conditionsmentioning
confidence: 99%